LOCATION BASED AGENDA NOTIFIER ON ANDROIDBASED MOBILE PHONE - Wahyu Adi Prakosa Mazharuddin Shiddiqi, Ary; Ayu Sinthia A., Putu; Titi Ciptaningtyas, Henning (Proceedings of KNASTIK, 2012)
People usually have their agenda noted on their mobile phones as it is able toremind the owner about the agenda. However, the ordinary agenda can onlyprovide information of the agenda detail without location map. This research aimsto create an application to provide detailed information as well as locationinformation of an agenda using Google Maps. In addition, this application is alsocapable of providing position information to the current user and shortest route tothe location of an event noted on the mobile phone agenda. Experiment results showthat the technique is able to provide information on the agenda with sufficientinformation about the location in term of map view and shortest route to arrive atthe event. This application has also been successfully implemented on manydifferent versions of Android and can also be run with either various types ofexisting telecommunications provider.